2009
DOI: 10.1590/s0102-09352009000300018
|View full text |Cite
|
Sign up to set email alerts
|

Carcass quality of feedlot finished steers fed yeast, monensin, and the association of both additives

Abstract: To evaluate the effects of the supplementation of feed additives on carcass quality in beef cattle, 72 Nellore steers (339.5kg, 20-month old) were feedlot finished and fed for 91 days one of the following diets: 1) control with no additives; or added of 2) live yeast culture; 3) monensin; or 4) the association of both additives. After slaughter, renal, pelvic, and inguinal fat and hot carcass weights were recorded and carcass was split into muscle, bone, and trimmable fat. Carcass Longissimus muscle area and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
2
11
1
7
Order By: Relevance
“…Os diferentes aditivos utilizados atualmente na nutrição de ruminantes apresentam poucos efeitos diretos sobre as características de carcaça, como já relatado em outros artigos. Gomes et al (2009), realizaram experimento com o objetivo de avaliar o efeito da inclusão de monensina e levedura sobre a qualidade da carcaça de bovinos terminados em confinamento e concluíram que o fornecimento de monensina, levedura ou a associação de ambos na dieta não exerce efeitos importantes sobre características de carcaça e da carne. Os autores afirmam ainda que a inclusão destes aditivos não promovem melhorias em peso de carcaça, rendimento de carne na carcaça e no teor de gordura da carcaça, que é um indicativo do grau de marmoreio.…”
Section: Resultados E Discussaounclassified
“…Os diferentes aditivos utilizados atualmente na nutrição de ruminantes apresentam poucos efeitos diretos sobre as características de carcaça, como já relatado em outros artigos. Gomes et al (2009), realizaram experimento com o objetivo de avaliar o efeito da inclusão de monensina e levedura sobre a qualidade da carcaça de bovinos terminados em confinamento e concluíram que o fornecimento de monensina, levedura ou a associação de ambos na dieta não exerce efeitos importantes sobre características de carcaça e da carne. Os autores afirmam ainda que a inclusão destes aditivos não promovem melhorias em peso de carcaça, rendimento de carne na carcaça e no teor de gordura da carcaça, que é um indicativo do grau de marmoreio.…”
Section: Resultados E Discussaounclassified
“…carcass characteristics were also variable; no improvement of carcass traits and meat quality of feedlot finished steers (Mir and Mir, 1994;Hinmann et al, 1998;Gomes et al, 2009), or finished goats (Whitley et al, 2009;Titi et al, 2008a). Addition of yeast culture in finish diet reduced meat/bone ratio and tissue protein in lambs and goats, increased fat content in lambs but not in goats (Titi et al, 2008a).…”
Section: Combination Of Yeast and Herbs On Beef Cattle Carcass (P Mamentioning
confidence: 99%
“…Feeding yeast culture has no effect on dry matter intake (DMI), live weight gain (LWG) or feed conversion ratio (FCR) of steers (Cabrera et al, 2000;Gomes et al, 2009), buffalo (Mahyuddin and Widiawati, 2010), male dairy calves (Titi et al, 2008b) or finishing lambs (Kawas et al, 2007a;Kawas et al, 2007b;Titi et al, 2008a) and kids (Titi et al, 2008a), goats (Whitley et al, 2009) or buffalo calves (Ramirez et al, 2007). However, Haddad and Goussous (2005) and Tripathy et al, (2010) found supplementation of yeast culture in lambs increased LWG, DMI, and DM digestibility in yeast-supplemented lambs observed by Haddad and Goussous (2005) , but were not found by Tripathy et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to SMITH et al (2009) andGOMES et al (2009), the greater the amount of energy that cattle consume, the higher the proportion of subcutaneous fat and consequently the more intramuscular fat there is in the meat, resulting in greater meat tenderness in the final product, an important factor for consumers. Boito et al Bovine carcasses exhibit many differences (DONICHT et al 2001).…”
Section: Introductionmentioning
confidence: 99%